1993
DOI: 10.1111/j.1432-1033.1993.tb17922.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase 2A associated with polyomavirus small‐T or middle‐T antigen is an okadaic acid‐sensitive tyrosyl phosphatase

Abstract: Papovavirus tumor antigens have been shown to associate with the cellular phosphoserinehreonine-specific protein phosphatase 2A (PP2A). We were interested in the consequences that Tantigen association might have on PP2A activity and so studies of the phosphatase activity in immunoprecipitates, prepared from polyoma virus-transformed or polyoma virus-infected mouse 3T3 fibroblasts, were performed. The phosphoserine/threonine phosphatase activity, measured with phosphorylase a as the substrate, showed all the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…Cayla and coworkers had previously analysed immunoprecipitates of an undetermined mixture of polyomavirus middle and small tumor antigens (Cayla et al, 1993). They found that the ratio of PP2A activity in these immunoprecipitates towards phosphorylase a and a cdc2-phosphorylated retinoblastoma protein peptide was similar to that obtained for biochemically puri®ed A/C heterodimer.…”
Section: Immunoprecipitation Of Trimeric Pp2a Complexes From Cellsmentioning
confidence: 94%
“…Cayla and coworkers had previously analysed immunoprecipitates of an undetermined mixture of polyomavirus middle and small tumor antigens (Cayla et al, 1993). They found that the ratio of PP2A activity in these immunoprecipitates towards phosphorylase a and a cdc2-phosphorylated retinoblastoma protein peptide was similar to that obtained for biochemically puri®ed A/C heterodimer.…”
Section: Immunoprecipitation Of Trimeric Pp2a Complexes From Cellsmentioning
confidence: 94%
“…The preparation and phosphorylation of the substrate and the assay conditions were as described [23].…”
Section: Phosphatase Assaysmentioning
confidence: 99%
“…Moreover, a family of papovavirus PP2A regulatory subunits exists that includes simian virus 40 and polyomavirus small tumor antigens and polyomavirus middle tumor antigen (MT) (Pallas et al, 1990). In all these cases, the PP2A core A/C heterodimer is found complexed with the regulatory subunit, and the substrate specificity and activity of PP2A are modulated (Yang et al, 1991;Cayla et al, 1993;Cegielska et al, 1994;Kamibayashi et al, 1994;Mayer-Jaekel et al, 1994;Ogris et al, 1997;Moreno et al, 2000).…”
Section: Introductionmentioning
confidence: 99%